Flexible Indium‐Tin‐Oxide Homojunction Thin‐Film Transistors with Two In‐Plane Gates on Cellulose‐Nanofiber‐Soaked Papers. (31st May 2019) - Liu, Zehua; Nie, Sha; Luo, Jie; Gao, Ya; Wang, Xiangyu; Wan, Qing
Abstract: Flexible indium‐tin‐oxide (ITO)‐based homojunction thin‐film transistors (TFTs) are fabricated on cellulose‐nanofiber‐soaked paper substrates. The paper is simultaneously used as the gate dielectric and substrate. Source/drain electrodes and a channel layer are sputtered by one‐step radio‐frequency sputtering deposition. The paper exhibits a very large specific electric‐double‐layer capacitance of 2.3 µF cm −2 due to the existence of mobile protons. The flexible ITO‐based TFTs can operate at a low voltage of 2.0 V and show a relatively high I ON / I OFF ratio of 7.5 × 10 6 . Furthermore, no obvious electrical degradation is observed at various bending radii. Finally, inverter and NAND logic operation are demonstrated by the TFTs together with two in‐plane gates. Such flexible homojunction TFTs on low‐cost and biodegradable paper are promising for portable paper electronics. Abstract : Homojunction thin‐film transistors (TFTs) are fabricated on cellulose‐nanofiber‐soaked paper substrates. The TFTs, which are based on indium tin oxide (ITO) are flexible and can operate at a low voltage, and the paper is simultaneously used as the gate dielectric layer and the substrate. NAND logic operation is demonstrated by using the TFTs with two in‐plane gates.